Linear Psoriasis - Agarwalla Arun; Joshi Arun; Agrawal Sudha; Jacob Mary; Garg Vijay K; Thakur Amarnath (Wolters Kluwer Medknow Publications, 2001)
Linear psoriasis, inflammatory linear varrucous epidermal naevus (ILVEN). Lichen straitus, linear lichen planus and invasion of epidermal naevi by psoriasis have clinical and histopathological overlap. We report two young male patients of true linear psoriasis without classical lesions elsewhere which were proved histopathologically. Seasonal variation and good response to topical antipsoriatic treatment supported the diagnosis.